2001
DOI: 10.1006/mpev.2001.0993
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogenies of Fig Wasps: Partial Cocladogenesis of Pollinators and Parasites

Abstract: Figs (Ficus spp., Moraceae) and their pollinating wasps form an obligate mutualism, which has long been considered a classic case of coevolution and cospeciation. Figs are also exploited by several clades of nonpollinating wasps, which are parasites of the mutualism and whose patterns of speciation have received little attention. We used data from nuclear and mitochondrial DNA regions to estimate the phylogenies of 20 species of Pleistodontes pollinating wasps and 16 species of Sycoscapter nonpollinating wasps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
125
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(128 citation statements)
references
References 86 publications
2
125
0
1
Order By: Relevance
“…Under such circumstances, both leaf-feeding and flower-infesting moths are provided with multiple available hosts, but the latter are more selective in their host choice owing to a broader range of coevolutionary traits with which they are constrained. The occurrence of multiple co-flowering host species is also the case in figs, for which preliminary analysis of host specificity in pollinating and non-pollinating fig wasps suggested that the former tends to be more host-specific (Weiblen & Bush 2002;Marussich & Machado 2007; but see Lopez-Vaamonde et al 2001;Jousselin et al 2006Jousselin et al , 2008.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Under such circumstances, both leaf-feeding and flower-infesting moths are provided with multiple available hosts, but the latter are more selective in their host choice owing to a broader range of coevolutionary traits with which they are constrained. The occurrence of multiple co-flowering host species is also the case in figs, for which preliminary analysis of host specificity in pollinating and non-pollinating fig wasps suggested that the former tends to be more host-specific (Weiblen & Bush 2002;Marussich & Machado 2007; but see Lopez-Vaamonde et al 2001;Jousselin et al 2006Jousselin et al , 2008.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast to their pollinating relatives, each of these cheater species has evolved to use four to six yucca hosts (Pellmyr 1999;Segraves & Pellmyr 2004), suggesting that host specificity in the pollinators may not be determined solely by the herbivorous habit of the moths (Pellmyr 2003). In the fig system, non-pollinating agaonid wasps that are closely related to and co-occur with pollinating fig wasps tend to be less host specific than are the pollinators (Weiblen & Bush 2002;Marussich & Machado 2007; but see Lopez-Vaamonde et al 2001;Jousselin et al 2006Jousselin et al , 2008. In addition, fig herbivores in general are dominated by insects that feed on several locally available fig hosts (Novotny et al 2002(Novotny et al , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…DNA was extracted from a single hind leg of most specimens using a simple Chelexbased protocol (Lopez-Vaamonde et al 2001). Based on prior experience (though not a hard 265 and fast rule), for insects less than 2 mm long we extracted DNA from the whole wasp using the DNeasy Tissue Kit (QIAGEN cat.…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
“…Slight cheats that arise by mutation could gradually erode the mutualistic interaction, and lead to dissolution or reciprocal extinction (Roberts and Sherratt 1998;Doebeli and Knowlton 1998). Although cheating has been assumed to be under strict control, recent empirical findings (reviewed by Bronstein 2001b) indicate that cheating is rampant in most mutualisms; in some cases, cheaters have been associated with mutualisms over long spans of evolutionary time (Després and Jaeger 1999;Pellmyr and Leebens-Mack 1999;Lopez-Vaamonde et al 2001). Recent theoretical advances have increased our understanding of the ecological and evolutionary persistence of particular forms of mutualism (e.g., Holland and DeAngelis 2001;Law et al 2001;Yu 2001;Holland et al 2002;Morris et al 2003;Wilson et al 2003).…”
Section: Factors That Influence the Persistence Of Mutualismsmentioning
confidence: 99%